The positive effect of JAK inhibitor tofacitinib in the treatment of primary Sjögren’s syndrome: a clinical case - D.G. Rekalov; I.O. Daniuk (Bolʹ, Sustavy, Pozvonočnik, 2023)
Primary Sjögren’s syndrome (pSS, Sjögren’s disease) is a systemic autoimmune disease which develops in previously healthy individuals and characterized by damage to exocrine glands, mainly lacrimal and salivary glands, with gradual formation of their secretory insufficiency and various systemic manifestations. According to EULAR recommendation (2019) therapeutic management of pSS bases on symptomatic treatment of sicca syndrome and broad-spectrum immunosuppression for systemic manifestations. The perspective group for the treatment of autoimmune disease is Janus kinase inhibitors, which can block the signals from biologically active molecules (interferons, erythropoietins and cytokines) and providing a response to these target cell signals. Therefore, the use of JAK inhibitors in patients with pSS requires clinical confirmation of effectiveness. The article described the clinical case of the positive effect of tofacitinib with methotrexate combination in the treatment of patient with pSS. A 55-year-old female with sicca syndrome (confirmed by Schirmer’s test), arthralgia, low-grade fever, weight loss and a positive test for the detection of specific antibodies (SS-A/Ro > 240 units/ml, SS-B/La 94 units/ml) was diagnosed with pSS. The total score of EULAR Sjögren’s syndrome disease activity index (ESSDAI) was 9 (activity grade II). The treatment included symptomatic methods of sicca syndrome correcting (replacement therapy with artificial tear preparations and chewing gums with xylitol) in combination with immunosuppressive therapy. The addition of tofacitinib 5 mg twice daily to methotrexate (10 mg weekly) has been shown to significantly reduce disease activity after 6 months of treatment (ESSDAI = 0).